Perancangan Desain Karakter Webcomic Arkana: Stellar Awakening Berdasarkan Kisah Mahabharata - Syafiq, Alfie Ade Riyan; Ayuswantana, Alfian Candra; Romadhona, Mahimma (Universitas Pahlawan Tuanku Tambusai, 2024)
The strawberry generation is a popular term in Taiwan which is used to indicate the generation after 1981 who have creative characteristics but are mentally fragile. As a result of the development of technology and foreign culture, the younger generation is becoming less concerned with their own culture, which in fact has a lot of potential in building the character and morals of the younger generation. Among them is the cultural art of shadow puppetry, which apart from providing entertainment also has the function of conveying moral messages about the primacy of life so that it can become a character based on one of the famous great epics, namely the Mahabharata, which contains many educational elements that teach about morals and character. both of which will later be transformed into modern webcomic media using the ATUMICS method. It is hoped that by designing the character designs for the webcomic Arkana: Stellar Awakening, it can provide various kinds of moral education from the Mahabharata story which can help the younger generation in building their good character.